1992
DOI: 10.1021/bi00142a002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of thymosin .beta.4 with muscle and platelet actin: implications for actin sequestration in resting platelets

Abstract: Quantitative measurements of the interactions of T beta 4 with muscle actin suggest that its only physiological role is monomer sequestration. T beta 4 forms a 1:1 complex with monomeric actin under physiological salt conditions. Its Kd for actin is not affected by calcium. T beta 4 binds only to actin monomers and not to filament ends or alongside the filament. T beta 4-actin complexes do not elongate actin filaments at either the barbed or the pointed end, and, unlike actobindin, T beta 4 does not specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
152
1
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(172 citation statements)
references
References 55 publications
(64 reference statements)
15
152
1
4
Order By: Relevance
“…Apparently, actin bound to thymosin ␤ 4 is participating in the polymerization process, either during nucleation or elongation. Previous investigators have suggested that this might also be the case in the absence of jasplakinolide (7), but others have not found evidence for anything other than monomer sequestration by thymosin ␤ 4 (20). A previous report (21) that thymosin ␤ 4 -actin complexes could directly associate with phalloidin-stabilized actin neglected the fact that phalloidin, like jasplakinolide, lowers the critical concentration and therefore decreases the amount of actin sequestered by thymosin ␤ 4 (17).…”
Section: The Effects Of Jasplakinolide On the Time Course Of Actin Pomentioning
confidence: 99%
“…Apparently, actin bound to thymosin ␤ 4 is participating in the polymerization process, either during nucleation or elongation. Previous investigators have suggested that this might also be the case in the absence of jasplakinolide (7), but others have not found evidence for anything other than monomer sequestration by thymosin ␤ 4 (20). A previous report (21) that thymosin ␤ 4 -actin complexes could directly associate with phalloidin-stabilized actin neglected the fact that phalloidin, like jasplakinolide, lowers the critical concentration and therefore decreases the amount of actin sequestered by thymosin ␤ 4 (17).…”
Section: The Effects Of Jasplakinolide On the Time Course Of Actin Pomentioning
confidence: 99%
“…The relatively low affinity of T~4 for actin (ca. 1 ~tM [4]) may be functionally significant in allowing the instant release of polymerizable actin into cytoplasm, if required.…”
Section: In~oductionmentioning
confidence: 99%
“…2.5 nM [8]), a much higher concentration was found inside cells (ca. 600 ,uM in the cytoplasm of platelets [7,9]). This led to the suggestion that the main physiological role of j&thymosins may be other than in modulating immune activities.…”
Section: Introductionmentioning
confidence: 99%